Relatos de agressões, abusos e maus tratos durante a graduação em medicina: um estudo transversal conduzido durante a Pandemia de COVID-19 - Santos , Thomás Luiz (2021)
Introduction: Studies show a high prevalence of aggression, abuse and mistreatment against medical students, and indicate that exposure to violence has an adverse impact on students' mental health. Studies on this problem in Brazil are scarce. This study aimed to assess the students' perception of aggression, abuse and mistreatment during medical graduation, as well as to identify the perpetrators and the main violence types, and correlate academic and sociodemographic variables with aggression types. Methodology: Educational, observational, cross-sectional and quantitative study carried out on Minas Gerais’s medical students enrolled in the 3rd through to the 12th terms between November 1, 2020, and March 31, 2021. An online questionnaire was sent to all students; replies were obtained from 264 respondents, 237 of which were included in the analysis. Results: The main violence perpetrators were students themselves with 89.2%, followed by teachers with 87.1%. The most frequent aggression types reported were depreciation or humiliation with 77.9%, and negative comments for being a student in the course with 71.7%. Our study found that 67.2% of the respondents were unaware of the existence of psychological support centers for medical students in their institutions. A higher frequency of psychological violence (96.2%) and sexual violence (67.6%) against the female gender, as well as a higher frequency of verbal violence (68.9%), psychological violence (97%) and sexual violence (68.2%) among respondents dissatisfied with their appearance, were found statistically significant. Physical aggression was reported by 4.2% of the respondents, and the threat of physical aggression by 10.4% of respondents. Conclusion: the perceived frequency of aggression, abuse and mistreatment was high among the population studied. Depreciation or humiliation was the most frequent aggression type, and students themselves were the main perpetrators, closely followed by teachers. Institutions must define a code of proper ethical conduct that is known by students and faculty alike, and that there are ombudspersons trained in attentive listening to students and effective response to possibly experienced situations of violence